Determining the electrochemical transport parameters of sodium-ions in hard carbon composite electrodes. (1st January 2022) - Ledwoch, D.; Komsiyska, L.; Hammer, E-M.; Smith, K.; Shearing, P.R.; Brett, D.J.L.; Kendrick, E.
Abstract: Sodium-ion batteries offer advantages over conventional Li-ion batteries, including cost and safety. However, much less is known about their operation and performance properties, particularly at the anode. The electron and ion transport in the active materials and composite electrode significantly impact battery performance. Understanding the changes in transport properties as a function of state-of-charge and state-of-health is essential for effective electrode design and performance assessment. In this work, the resistivity and diffusivity of sodium transport in hard carbon composite electrodes are studied at different states-of-health, using Galvanostatic Intermittent Titration Technique (GITT), Electrochemical Impedance Spectroscopy (EIS), and Electrochemical Potential Spectroscopy (EPS) in a stable 3-electrode test cell configuration. The reference electrode eliminated some voltage errors arising from the overpotentials on the counter electrode. The resistance contributions from the surface electrolyte interface, electrolyte transport in the electrode pores, and the charge transfer resistance are extrapolated from the impedance measurements and the diffusion coefficient from the GITT and EPS. The different techniques indicate similar trends in the diffusion coefficient during sodiation, desodiation, and ageing, although different orders of magnitude were observed between the EPS and GITT data. The accuracy of the parameters calculated using the different electrochemical techniques is discussed in detail.